The Paradox of Negative Antibody Screening and Positive Crossmatching: Implications for Transfusion Safety in a Developing Country - Suryanto; Adang Muhammad Gugun (HM Publisher, 2025)
Modern antibody screening is a pillar of transfusion safety, intended to prevent hemolytic reactions. However, its ultimate effectiveness, particularly in diverse populations within developing nations where abbreviated crossmatch protocols are not feasible, remains a critical question. This study investigates the